The Influence of the Learning Environment on the Learning Achievement of Students of the Economics Education Study Program Class of 2018 UNESA - Shafa Annastasya (Buana Pendidikan, 2023)
A person's learning achievement can be affected by certain factors, one of them is the learning environment, where the learning environment itself includes 3 aspects, consisting of the campus environment, community environment, and family environment. This research aims to investigate the influence of the learning environment on student achievement in the economic education study program. In this research, quantitative explanatory methods were used to examine the relationship between the campus environment, community environment, familiy environment, and student achievement. Students of the 2018 economic education study program, totaling 63 people, became the population in this research. Data were collected through a questionnaire method with multiple linear regression analysis using SPSS version 26 application as a data analysis technique. The findings show that: (1) the family environment partially has a positive influence on student achievement; (2) the campus environment partially has a positive influence on student learning achievement; (3) the community environment partially does not affect student learning achievement; (4) the family environment, campus environment, community environment simultaneously have a positive and significant effect on student achievement.